Human Brain-Based Models Provide a Powerful Tool for the Advancement of Parkinson’s Disease Research and Therapeutic Development - McComish, Sarah F.; MacMahon Copas, Adina N.; Caldwell, Maeve A. (Frontiers in Neuroscience, 2022)
Parkinson’s disease (PD) is the second most common neurodegenerative disease and affects approximately 2-3% of the population over the age of 65. PD is characterised by the loss of dopaminergic neurons from the substantia nigra, leading to debilitating motor symptoms including bradykinesia, tremor, rigidity and postural instability. PD also results in a host of non-motor symptoms such as cognitive decline, sleep disturbances and depression. Although existing therapies can successfully manage symptoms for several years, there is still no means to halt progression of this severely debilitating disorder. Animal models used to replicate aspects of PD have contributed greatly to our current understanding but do not fully replicate pathological mechanisms as they occur in patients. Because of this, there is now great interest in the use of human-based models to help further our understanding of disease processes. Human-based models include those derived from embryonic stem cells, patient-derived induced pluripotent stem cells and brain organoids, as well as post mortem tissue. These models facilitate in vitro analysis of disease mechanisms and it is hoped they will help bridge the existing gap between bench and bedside. This review will discuss the various human-based models utilised in PD research today and highlight some of the key breakthroughs they have facilitated. Furthermore, the potential caveats associated with the use of human-based models will be detailed.